Synthesis of NiO Nanoparticles as a Catalyst in Transesterification Reaction from Used Cooking Oil for Biodiesel Production - Hasri; Putri, Suriati Eka; Negara, Satria Putra Jaya; Afni, Nur; Anwar, Fadil (Science and Technology Indonesia, 2026)
This study aims to synthesize and characterize nickel oxide (NiO) nanoparticles as heterogeneous catalysts for biodiesel production from used cooking oil through transesterification. The synthesis was conducted using the sol-gel method with NiCl2·6H2O as a precursor and NaOH as an alkaline agent. Characterizations were then performed using Particle Size Analysis (PSA), X-ray Diffraction (XRD), Scanning Electron Microscopy with Energy Dispersive Spectroscopy (SEM-EDS), and Specific Surface Area (SAA) analysis. The PSA results showed that the samples had an average particle size of 37.0 nm with a narrow distribution (PDI = 0.010). XRD confirmed a cubic crystal structure corresponding to JCPDS No. 47-1049, while SEM images showed revealed uniform spherical morphology. In addition, EDS analysis verified the composition of Ni and O as the main elements. The SAA of 489.26 m2/g showed high catalytic activity potential. Catalyst performance tests with methanol-to-oil molar ratios of 1:3, 1:6, and 1:9 showed the highest biodiesel yield of 97.79% at a 1:9 ratio. The produced biodiesel met the Indonesian National Standard (SNI 7182:2015) with a density of 0.86–0.89 g/mL, acid number of 0.40–0.50 mg KOH/g, iodine number of 67.73–93.13 g I2/100 g, and cetane number of 76.87–114.86. GC-MS analysis showed methyl ester chains between C15–C21, confirming compliance with APEC standards. Based on these results, NiO nanoparticles showed high efficiency as an eco-friendly heterogeneous catalyst for biodiesel production.